Idiopathic Hirsutism and Insulin Resistance. (20th October 2013) - Talaei, Afsaneh; Adgi, Zahra; Mohamadi Kelishadi, Mahnaz
Abstract : Background and Objectives . Polycystic ovary syndrome (PCOS) and idiopathic hirsutism (HI) are the two most common causes of hirsutism. Insulin resistance plays a key role in PCOS, but there are not enough data showing that patients with HI also have insulin resistance. This study was designed to evaluate the presence of insulin resistance in women with HI. Methods . Based on a cross-sectional study, two groups of age-BMI matched, hirsute women were compared to age-BMI matched, nonhirsute women. Sixty nonobese women with PCOS, thirty nonobese women with HI, and sixty nonobese control women were included in the study. Samples of hormones including androgens were measured. Insulin resistance based on homeostasis model assessment of insulin resistance (HOMA-IR) was compared between three groups by the Kruskal-Wallis test. Results . Patients with PCOS had significantly higher basal insulin level (16.04 ± 1.4 versus 7 . 32 ± 6.85 μ Iu/mL) and HOMA-IR score (3.7 ± 3.36 versus 1.75 ± 1.67 ) than patients with HI (P 0.001 ). Patients with HI also had significantly higher basal insulin level and HOMA-IR score than control group (P 0.001 ). Conclusion . Our data suggest that both PCOS and HI are associated with insulin resistance and these patients are more insulin resistant than healthy control people.